Kompetensi Profesional Guru BK Dalam Pelaksanaan Layanan Bimbingan dan Konseling di Institusi Pendidikan - Ahmad Yasri; Yenti Arsini; Bastothum Ikhsan (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Â Guidance and counseling is the counselor (counselor) offering assistance to people (clients) done directly and causing a reciprocal relationship so that the client has knowledge or a place so he can find out and solve his problem. As stated in Law No. 20 of 2003 concerning the National Education System Article 1 No. 6, counseling guidance is recognized as a legal unit as a qualification of educators, consisting of instructors, lecturers, guardians. Identified 4 educators from government regulation no. 19 of 2005 concerning National Education Standards Article 28 Point 3 and RI Law No. 14 of 2005 regarding teachers, lecturers. a teacher or lecturer must have, and be able to practice, and master the knowledge, abilities, and attitudes known as competence to carry out their professional duties.